Effect of co-site dilution on the magnetism of RCo5 (R = Gd, Y) compounds. (28th March 2018) - Nikitin, S A; Bogdanov, A E; Morozkin, A V; Knotko, A V; Yapaskurt, V O; Ovchenkova, I A; Smirnov, A V; Nirmala, R; Quezado, S; Malik, S K
Abstract: The magnetic and magnetocaloric properties of the R Co5− x Ga x ( R  = Gd, Y; x = 1, 1.5, 1.6, 1.7) compounds have been studied. X-ray and electron microprobe analysis show that the samples are single phase and crystallize in the hexagonal CaCu5 - type structure (space group P 6/ mmm, N 191, hP 6). The magnetic properties have been studied from 2 to 400 K under magnetic fields in the region of 1 to 140 kOe. With increasing Ga amount the magnetic ordering temperature decreases rapidly. The increase in Ga concentration leads to the reduction of the magnetic moment of Co sublattice and the Curie temperature. It has been found that the paramagnetic susceptibility follows the Néel-type law for GdCo5− x Ga x (x = 1.5, 1.6, 1.7) and the Curie-Weiss law for YCo3.3 Ga1.7 . The molecular field coefficients and sublattice magnetizations were determined on a basis of the Néel theory and experimental data. The magnetocaloric effect and refrigerant capacity have been estimated over a wide temperature range of 10–350 K.